2022
DOI: 10.4103/jehp.jehp_1019_21
|View full text |Cite
|
Sign up to set email alerts
|

Nurses in NICUs’ views on nosocomial infection prevention

Abstract: BACKGROUND: Basic infection control measures are required in India's health-care setting in Neonatal Intensive Care Units (NICUs) to lower the prevalence of hospital-associated infections. The aim of the present study was to assess practices followed by nurses of NICUs for nosocomial infection prevention. MATERIALS AND METHODS: From January to February 2020, a descriptive cross-sectional study was conducted. Participants in the study were chosen by tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…According to Gulia et al, only a moderate grasp of HAI prevention was reported by 70% of NICU nurses. In NICUs, nurse practices for preventing HAI were effective (60%) [15]. Kakkar et al examined the preintervention KAP of 105 nurses.…”
Section: Discussionmentioning
confidence: 99%
“…According to Gulia et al, only a moderate grasp of HAI prevention was reported by 70% of NICU nurses. In NICUs, nurse practices for preventing HAI were effective (60%) [15]. Kakkar et al examined the preintervention KAP of 105 nurses.…”
Section: Discussionmentioning
confidence: 99%